2018
DOI: 10.1175/jcli-d-18-0034.1
|View full text |Cite
|
Sign up to set email alerts
|

The Northeast Winter Monsoon over the Indian Subcontinent and Southeast Asia: Evolution, Interannual Variability, and Model Simulations

Abstract: The northeast monsoon (NEM) brings the bulk of annual rainfall to southeastern peninsular India, Sri Lanka, and the neighboring Southeast Asian countries. This October–December monsoon is referred to as the winter monsoon in this region. In contrast, the southwest summer monsoon brings bountiful rainfall to the Indo-Gangetic Plain. The winter monsoon region is objectively demarcated from analysis of the timing of peak monthly rainfall. Because of the region’s complex terrain, in situ precipitation datasets are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…And in the shoulder seasons of winter, i.e., preceding fall and subsequent spring is it even adequately characterized? Answers are sought from analyses of century-long (1901-2016) SST and precipitation records as realistic representations of regional hydroclimate variability still elude climate system models, at least, of the IPCC-AR5 genre (Sengupta & Nigam, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…And in the shoulder seasons of winter, i.e., preceding fall and subsequent spring is it even adequately characterized? Answers are sought from analyses of century-long (1901-2016) SST and precipitation records as realistic representations of regional hydroclimate variability still elude climate system models, at least, of the IPCC-AR5 genre (Sengupta & Nigam, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the teleconnections exhibited by the winter anomalies over northern India in this paper is consistent with such an interpretation. In this study, a robust negative correlation is shown between the winter rainfall anomalies over southeastern India with the tropical Pacific, which at the outset seems contrary to previous studies (Rajeevan et al ., ; Sengupta and Nigam, ). However, the earlier studies have reported comparatively much weaker correlations and have used a different season for IWM (e.g., October–November–December).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, despite the strong variability of the Indian Winter Monsoon (IWM) rainfall and its relatively strong teleconnection with ENSO (Ramaswamy, 1972;Zubair and Ropelewski, 2006;Kumar et al, 2007;Rajeevan et al, 2012;Dimri et al, 2016;Misra and Bhardwaj, 2019;Sengupta and Nigam, 2019) the models continue to display poor fidelity of the IWM (Rajeevan et al, 2012;Sengupta and Nigam, 2019).…”
mentioning
confidence: 99%
“…An anomalous anticyclonic circulation over the Bay of Bengal is observed in the wind regression pattern. This anticyclone is forced by the reduction of deep convection over the Maritime continent which is related to El Nino (Sengupta et al, 2019). Due to this anticyclonic circulation, the number of tropical cyclones forms over Bay of Bengal is below (above) normal during El Nino year (La Nina year) (Girshkumar et al2015).…”
Section: Observed Sst-wind-rainfall Anomalies Associated With El Ninomentioning
confidence: 99%